An Analysis of Malocclusion and Occlusal Characteristics in Nepalese Orthodontic Patients - Shrestha, Sujita; Shrestha, Rabindra Man (Orthodontic Journal of Nepal, 2013)
Objective: To analyze the prevalence of malocclusion and occlusal characteristics in referred Nepalese orthodontic patients with respect to age, gender, Angle’s classification. Materials & Method: Study models of 464 orthodontic patients (165 male and 299 female) of the age ranging from 11 to 30 years were studied to evaluate the prevalence of malocclusion using Angle’s classification and occlusal characteristics of overjet, overbite, open bite, cross bite, displacement, and hypodontia according to the method of Dental Health Component of Index of Orthodontic Treatment Need. The association between DHC grades and Angle’s classification and gender were assessed using chi-square test (p < 0.01). Result: The malocclusion status among the Nepalese seeking orthodontic treatment was 54.7% Class I, 36.9% Class II, and 8.4% Class III. The occurrence of occlusal discrepancies were overjet in 43.8%, increased overbite in 20.7%, open bite in 8.2%, cross bite in 23.3%, displacement in 65.7% and hypodontia in 11.3%. Conclusion: 16.2 % required no/little treatment need, 20.4% required borderline treatment need, and 63.4 % required great/severe treatment need according to DHC scale. There was statistically significant association between DHC grades and distribution of malocclusion and gender of the Nepalese subjects. DOI: http://dx.doi.org/10.3126/ojn.v3i1.9272 Orthodontic Journal of Nepal, Vol.3, No.1, 2013: 19-25